2001
DOI: 10.1002/jemt.1094
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar macrophage–T cell interactions during Th1‐type sarcoid inflammation

Abstract: Sarcoidosis is an immunomediated, multisystem disorder of unknown cause(s) characterized by a heightened Th1 immune response that leads to an uncontrolled granuloma formation at sites of disease activity. The past few years have seen outstanding advances in the understanding of immunological and molecular events involved in the pathogenesis of this disease. The idea is that several cytokines and chemokines, which are secreted at sites of disease activity, participate in granuloma formation. This paper describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 57 publications
0
27
0
Order By: Relevance
“…Notably, in the present study, Alveolar macrophages of patients with sarcoidosis exhibit multiple secretory cell functions in that they release other cytokines such as IL-15, growth factors, and chemokines such as monocyte chemotactic protein-1, RANTES (regulated, on activation, T-cell expressed and secreted) and macrophage inflammatory proteins-1a and -1b [2,26,27]. Thus, alveolar macrophages may strongly affect T-cell recruitment and T-cell response [28]. In turn, T-cells are also known to spontaneously release increased levels of some cytokines and chemokines, e.g.…”
Section: Discussionmentioning
confidence: 56%
“…Notably, in the present study, Alveolar macrophages of patients with sarcoidosis exhibit multiple secretory cell functions in that they release other cytokines such as IL-15, growth factors, and chemokines such as monocyte chemotactic protein-1, RANTES (regulated, on activation, T-cell expressed and secreted) and macrophage inflammatory proteins-1a and -1b [2,26,27]. Thus, alveolar macrophages may strongly affect T-cell recruitment and T-cell response [28]. In turn, T-cells are also known to spontaneously release increased levels of some cytokines and chemokines, e.g.…”
Section: Discussionmentioning
confidence: 56%
“…This is supported by studies finding CXCR3 expression on BAL lymphocytes from sarcoid patients [13]. Importantly, IL-2 has been found to be one of the most potent inducers of CXCR3 on lymphocytes [29], and multiple studies have suggested that IL-2 is pivotal in activating peripheral blood and BAL lymphocytes during pulmonary sarcoidosis [30][31][32][33][34].…”
Section: Patient Populationmentioning
confidence: 80%
“…This study was designed to determine whether there are augmented levels of IFN-inducible ELR -CXC chemokines in bronchoalveolar lavage fluid (BALF) from patients with the clinical/pathological diagnosis of pulmonary sarcoidosis, and resolve the current discrepancies within the literature [9][10][11][12][13]. Moreover, this study aimed to elucidate the cellular sources of specific IFN-inducible ELR -CXC chemokines and determine which cells express CXCR3 during the pathogenesis of pulmonary sarcoidosis.…”
Section: Bronchoalveolar Fluid (Balf)mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Th2 responses use the cytokines IL-5, IL-4, and IL-13, which enhance eosinophil and mast cell mobilization and cause certain allergic diseases such as asthma. In addition, Th1 responses may be counteracted by Th2 responses (1)(2)(3)(4)(5).…”
mentioning
confidence: 99%